Análisis de la planta turística, oferta alojamiento en las parroquias de Quitumbe – Chillogallo y Turubamba, cantón Quito, provincia de Pichincha. - Quezada Sanchez, John Alejandro (2022)
The purpose of this research study was to conduct an analysis of the tourist plant, lodging supply, and parishes of Quitumbe - Chillogallo and Turubamba. Three objectives were developed to achieve the research study. The first objective was to establish a situational diagnosis with the pertinent bibliographic review of web pages, books, journals, and scientific documents. In order to obtain a high level of veracity, the analytical method was used. It consists of separating all the information to understand it to make an assessment or situational diagnosis of the housing facilities in the parishes to be researched. In the second objective, the establishments were inventoried through interviews with the owners and/or employees, applying the inventory data sheets provided by the “Univerdidad Técnica de Cotopaxi”, Tourism career, allowing to conclude that the parishes of Quitumbe - Chillogallo and Turubamba have several lodging establishments with two typologies: hotels and hostels. With a total of 26 establishments, they offer different services according to their categories. It is also mentioned that there are 20 legal establishments, 9 in the parish of Quitumbe, 7 in the parish of Chillogallo and 4 in the parish of Turubamba, with all the pertinent procedures to be able to operate with their activities and 6 establishments that are not registered in the MINTUR cadastre, 4 in the parish of Quitumbe and 2 in the parish of Turubamba. Finally, in the third objective, all the information was systematized in the design of the catalog using the illustrator software for the purpose of disseminating information to domestic and foreign tourists.